Efficacy of Cognitive Instruction in Teaching Deictic Motion Verbs in EFL Classrooms - Hu, Ying-hsueh (International Journal of Learning, Teaching and Educational Research, 2015)
This study investigated an alternative pedagogy to teaching motion deixis, in particular, two English deictic verbs bring and take to EFL learners. Sixty-five first year students from a university in Northern Taiwan participated in a comparative experiment. They were divided into 1) a control group (CT), receiving implicit treatment with no particular rules explained, apart from Chinese translation, and 2) an experimental group, receiving explicit Cognitive Instruction (CI). Each group was treated with four sessions (30 minutes per session) of respective instruction, and a pre-test prior to and two post tests (one post-test and one delayed post-test) after the treatment were administered to gauge participants‟ performance. Results indicate that the CI group made significant improvements in both short-term and long-term recall, while the CT in short-term recall only. The findings support that CI instruction of vocabulary and grammar is beneficial, and even necessary, to some aspects of EFL learning, particularly those concerned with learning deixis concepts.